CRISPR/Cas9-mediated Serine protease 2 disruption induces male sterility in Spodoptera litura - Bi, Honglun; Xu, Xia; Li, Xiaowei; Wang, Yaohui; Zhou, Shutang; Huang, Yongping (Frontiers in Physiology, 2022)
Male fertility is essential for reproduction and population growth in animals. Many factors affect male fertility, such as courtship behavior, sperm quantity, and sperm motility, among others. Seminal Fluid Proteins (SFPs) are vital components of seminal fluid in the male ejaculate, which affect male fertility, sperm activation, and female ovulation. However, the knowledge of SFPs is insufficient; the function of many SFPs remains unknown, and most described functions were mainly characterized in Drosophila or other laboratory models. Here, we focus on the Serine protease 2 (Ser2) gene in the lepidopteran pest Spodoptera litura. The Ser2 gene was specifically expressed in male adults. Disruption of the Ser2 gene mediated by CRISPR/Cas9 induced male sterility but females remained fertile. PCR-based detection of the next-generation mutants showed that male sterility was stably inherited. The qRT-PCR analysis of SlSer2 mutants showed that motor protein family genes and structural protein family genes were down-regulated, while protein modification family genes were up-regulated, suggesting that SlSer2 may be involved in sperm movement and activity. These results demonstrate that Ser2 is an important component of SFPs in seminal fluid and was identified for a useful sterile gene for pest control that may lead to new control strategies for lepidopteran insect pests such as S. litura.